Gonçalves Dias, a escravidão e o tapete levantado - Marques, Wilton José [UNESP] (My University, 2013)
The article makes a reading of Meditation, by Antônio Gonçalves Dias, published in Guanabara magazine over the first half of 1850. In this work unfinished and unlike their romantic couples, the poet criticizes that slavery in Brazil.

O artigo faz uma leitura de Meditação, de Antônio Gonçalves Dias, publicada na revista Guanabara ao longo do primeiro semestre de 1850. Nessa obra inacabada e ao contrário de seus pares românticos, o poeta critica a escravidão no Brasil.
Keywords: Romanticism; Antônio Gonçalves Dias; Meditação; Slavery; Romantismo; Antônio Gonçalves Dias; Meditação; Escravidão